Intermittent waste heat recovery: Investment profitability of ORC cogeneration for batch, gas-fired coffee roasting - Pantaleo,AM; markides,C; fordham,J; Oyewunmi (Elsevier, 2017)
Coffee roasting is a highly energy intensive process with much of the energy being lost in intermittent cycles as discharged heatfrom the stack. In this work, combined heat and power (CHP) systems based on micro gas-turbines (MGT) are investigated forproviding heat to the roasting process. Much of the heat released in a coffee roaster is from the afterburner that heats up the fluegases to high temperatures in order to remove volatile organic compounds (VOCs) and other pollutants. An interesting solutionfor utilizing waste heat is assessed through energy and material balances of a rotating drum coffee roasting with partial hot gasrecycling. A cost assessment methodology is adopted to compare the profitability of three proposed system configurationsintegrated into the process. The case study of a major coffee torrefaction plant with 500 kg/h production capacity is assumed tocarry out the thermo-economic assessment, under the Italian energy framework. The CHP options under investigation are:(i) regenerative topping MGT coupled to the existing modulating gas burner to generate hot air for the roasting process;(ii) intermittent waste-heat recovery from the hot flue-gases through an organic Rankine cycle (ORC) engine coupled to athermal storage buffer; and (iii) non-regenerative topping MGT with direct recovery of turbine outlet air for the roasting processby means of an afterburner that modulates the heat demand of the roasting process. The results show that the profitability of theseinvestments is highly influenced by the natural gas/electricity cost ratio, by the coffee torrefaction production capacity and by theintermittency level of discharged heat. The MGT appears as a more profitable option than waste-heat recovery via the ORCengine due to the intermittency of the heat source and the relatively high electricity/heat cost ratio.